Implementasi Pengembangan Kurikulum Merdeka Berbasis Pertumbuhan Iman dan Kecakapan Hidup Anak Usia 4-6 Tahun di Oasis Malang - Kurniajaya, Fransiska; Hamzah, Amir (DIDAKTIKOS: Jurnal Pendidikan Agama Kristen, 2024)
This study focuses on the implementation of the results of the development of the Independent Curriculum based on the growth of faith and life skills of children aged 4 to 6 years in Oasis Malang. The Independent Curriculum is a learning approach that provides freedom and independence for students in exploring their potential and their environment. The Independent Curriculum in this study is implemented by paying attention to aspects of faith growth and development of life skills in early childhood (PAUD). The purpose of this study is to explain the implementation process of the development of the Merdeka Curriculum, analyze the impact or consequences on the growth of faith and life skills of students, and identify supporting and inhibiting factors in the implementation of this curriculum. The research approach method used is PAR ( Participatory Action Research), with data collection through interviews, observations and participation.The results of this study indicate that the implementation of the Merdeka Curriculum in Oasis Malang has gone well, with a focus on instilling values of faith, character building and developing life skills. The visible impacts or benefits are improvements in aspects of child development, such as independence, creativity, adaptability, and responsibility. The main supporting factors are commitment, school readiness, and parental involvement.The findings in this study can be input for early childhood education institutions (PAUD) in developing a curriculum that is appropriate to the needs and potential of students, while still paying attention to aspects of faith growth and development of life skills.